Uncovering Low-Level Maternal Gonosomal Mosaicism in X-Linked Agammaglobulinemia: Implications for Genetic Counseling - Rivière, Jacques G.; Franco-Jarava, Clara; Martínez-Gallo, Mónica; Aguiló-Cucurull, Aina; Blasco-Pérez, Laura; Paramonov, Ida; Antolín, María; Martín-Nalda, Andrea; Soler-Palacín, Pere; Colobran, Roger (Frontiers in Immunology, 2020)
X-linked agammaglobulinemia (XLA) is a clinically and genetically well-defined immunodeficiency and the most common form of agammaglobulinemia. It is characterized by susceptibility to recurrent bacterial infections, profound hypogammaglobulinemia, and few or no circulating B cells. XLA is caused by mutations in the BTK gene, which encodes Bruton's tyrosine kinase (BTK). Due to its X-linked recessive inheritance pattern, XLA virtually only affects males, and the mother is carrier of the mutation in 80% to 85% of males with this condition. In the remaining 15% to 20% of cases, the affected male is considered to have a de novo mutation. Here, we present the case of a child with a diagnosis of XLA caused by a missense mutation in the BTK gene (c.494G>A / p.C165Y). Apparently, his mother was wild-type for this gene, which implied that the mutation was de novo, but careful analysis of Sanger electropherograms and the use of high-coverage massive parallel sequencing revealed low-level maternal gonosomal mosaicism. The mutation was detected in various samples from the mother (blood, urine, buccal swab, and vaginal swab) at a low frequency of 2% to 5%, and the status of the patient’s mutation changed from de novo to inherited. This study underscores the importance of accurately establishing the parents’ status on detection of an apparently de novo mutation in a patient, as inadvertent low-level mosaicism may lead to misinterpretation of the risk of recurrence, vital for genetic counseling.